Intraoperative diagnosis of an anterior sacral meningocele mimicking a giant ovarian cyst in an adult - Hakan, Simsek (Vojnosanitetski pregled, 2020)
Introduction. Anterior sacral meningocele (ASM) is a very rare condition that is the herniation of the meningeal sac into the pelvic cavity through a developmental bone defect of the anterior wall of the sacrum. Most of the ASM are diagnosed in childhood but the reported cases that are diagnosed in adults exhibit a gamut of complications. Case report. We presented a case of ASM excision that was misdiagnosed as a giant ovarian cyst. A 28-year-old woman was admitted to the General Surgery Clinic and than to the Gynecology Department with suspect of ovarian cyst depending on ultrasonography (US) scans solely. Adnexial torsion was suspected and surgery to remove the cyst and adnexial exploration was planned. When the lesion was found out to be ASM, neurosurgery team tied the neck and excised the whole meningocele. Histopathologic evaluations confirmed dural sac. Neurological examinations right after the operation revealed 20% weakness in knee extension. It totally recovered in 6 months time. Her MR imaging studies and computed tomography (CT) scans revealed multiple ASM sacs and defects of the anterior wall of the sacrum. Conclusion. This case emphasizes the importance of utilizing available screening tools including CT andmagnetic resonance imaging (MRI) studies as the gold standard in addition to US scans in the preoperative period in order to accurately evaluate and characterize any pelvic lesion.